2000
DOI: 10.1359/jbmr.2000.15.4.770
|View full text |Cite
|
Sign up to set email alerts
|

Alfacalcidol Inhibits Bone Resorption and Stimulates Formation in an Ovariectomized Rat Model of Osteoporosis: Distinct Actions from Estrogen

Abstract: Although alfacalcidol has been widely used for the treatment of osteoporosis in certain countries, its mechanism of action in bone, especially in the vitamin D-replete state, remains unclear. Here we provide histomorphometric as well as biochemical evidence that alfacalcidol suppresses osteoclastic bone resorption in an ovariectomized rat model of osteoporosis. Furthermore, when compared with 17␤-estradiol, a representative antiresorptive drug, it is evident that alfacalcidol causes a dose-dependent suppressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1
7

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(56 citation statements)
references
References 35 publications
4
44
1
7
Order By: Relevance
“…Alfacalcidol (Chugai Pharmaceutical, Tokyo, Japan) was dissolved in medium-chain triglyceride (MCT) and a dose of 0.1 μg/kg/day or vehicle (MCT) alone was administered orally every day for 4 weeks. The dose of alfacalcidol was determined based on a previous study showing that this dose did not elevate serum calcium levels (39).…”
Section: Methodsmentioning
confidence: 99%
“…Alfacalcidol (Chugai Pharmaceutical, Tokyo, Japan) was dissolved in medium-chain triglyceride (MCT) and a dose of 0.1 μg/kg/day or vehicle (MCT) alone was administered orally every day for 4 weeks. The dose of alfacalcidol was determined based on a previous study showing that this dose did not elevate serum calcium levels (39).…”
Section: Methodsmentioning
confidence: 99%
“…(30,31) In rodent models, vitamin D analogues have been shown to increase bone mass, improve spatial architecture, and strengthen bones. (14)(15)(16)(17)32) Histomorphometry showed that vitamin D analogues can stimulate bone-formation activity on cortical and trabecular bone surfaces; however, bone-formation activity was best demonstrated at hypercalcemic doses. (14,15) Similarly in clinical studies, skeletal efficacy was demonstrated for vitamin D analogues, including reduction of nonvertebral fractures, (5)(6)(7) but the realization of bone efficacy in the absence of hypercalcemia or hypercalciuria has been difficult to achieve.…”
Section: Discussionmentioning
confidence: 99%
“…(5)(6)(7)(8) However, vitamin D analogues were shown to dose-dependently elevate calcium in sera and in urine, leading to concerns about hypercalcemia and hypercalciuria in humans (5,6,(9)(10)(11)(12)(13) and in animals. (14)(15)(16)(17)(18) ORIGINAL ARTICLE…”
Section: Introductionmentioning
confidence: 99%
“…Rats were orally administered vehicle or alfacalcidol (0.1 lg kg -1 ) (Chugai Pharmaceutical, Japan), 5 days a week during 6 weeks. This dose has been shown to inhibit bone resorption and enhance bone formation in ovariectomized rats treated for 5 weeks [25]. The 7-month-old rats did not receive any treatment.…”
Section: Animalsmentioning
confidence: 99%